Penerapan Etika Profesi Akuntan dan Kasus-kasus Pelanggaran Etika Profesi Akuntan - Saridawati Saridawati; Putra Aditya Muhammad; Rini Wanti Sholikhah; Dewi Nur Aini; Rini Mustikowati (Jurnal Akuntan Publik, 2024)
Accounting ethics is the study of ethical behavior in work contexts that require special knowledge and skills. Professional ethics involves upholding justice to provide comprehensive professional services to society and fulfill duties towards society. However, in the current era of technological progress and competition, there are many cases of violations of accounting professional ethics, with the discovery of many cases of business ethics violations in Indonesia, including PT Muzatek Jaya, PT Asuransi Jiwasraya, PT Garuda Indonesia (Persero). The aim of this research was to determine cases of violations of accounting professional ethics in Indonesia and used literature study methods such as Google Scholar, reference books and online media.